Cross‑sectional study of gastrointestinal helminthosis in goats from three ecosystems in Peru: Prevalence and associated factors - Castillo Doloriert, Hugo (2025)
Gastrointestinal parasitism is a health issue in livestock, particularly in non-intensive farming systems. This research evaluated the prevalence and risk factors associated with gastrointestinal helminths in goats from three ecosystems in Peru: the Andean shrubland (Ancash), dry forest (Lambayeque), and coastal valley (Lima). The study used a cross-sectional design, with random sampling of goats from extensive production systems in each ecosystem. A total of 819 fecal samples were collected and analyzed using qualitative and quantitative parasitological methods. Additionally, coproculture was performed to identify infective larvae of nematodes. The FAMACHA© index was used to assess anemia levels, while body condition scores were recorded to evaluate the nutritional status of the animals. The highest prevalence was recorded in the Andean shrubland (74.2%), followed by the dry forest (63.1%), whereas the coastal valley had the lowest prevalence (59.3%). The most frequently identified helminths were strongyle-type eggs (49.9%) and Skrjabinema sp. (33.7%), while Moniezia sp. (5.4%) and Fasciola hepatica (1.1%) were detected at lower frequencies. The identification of L3 infective larvae of Haemonchus sp., Trichostrongylus sp., Cooperia sp., Strongyloides sp., Oesophagostomum sp., Bunostomum sp., and Teladorsagia sp. highlighted the diversity of gastrointestinal nematodes affecting goats in Peru. Multivariable analysis revealed that anemia (FAMACHA ≥ 3; PR = 1.14), poor body condition (BCS 1–2; PR = 1.03), and age (2–6 teeths or full dentition; PR = 1.12 and 1.08, respectively) were associated with increased infection risk. Males had lower prevalence than females (PR = 0.80), and goats raised in the dry forest and coastal valley had lower risk than those from the Andean shrubland. These findings highlight the influence of physiological status and environmental conditions on parasite burden in goat herds.